1989
DOI: 10.2307/1130777
|View full text |Cite
|
Sign up to set email alerts
|

Children's Responses to Angry Adult Behavior as a Function of Marital Distress and History of Interparent Hostility

Abstract: Responses of 2-5-year-old children to angry adult behavior were examined as a function of parental report of marital distress, history of interparent verbal hostility, and history of interparent physical hostility. A trained actor engaged the child's mother in an emotionally expressive verbal exchange while the child played in the same room. The exchange was standardized and consisted of a 7-episode sequence of shifting background conditions (no emotion, friendly, no emotion, angry, no emotion, reconciliation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 20 publications
5
103
1
2
Order By: Relevance
“…Cummings, Pellegrini, Notarius, & Cummings, 1989; O'Brien, Margolin, John, & Krueger, 1991). In a similar vein, Katz and Gottman (1994) use the developmental context of the marriage to account for their finding that a withdrawn marital interaction style, but not a "hot" engaged style, is associated with child anger; they posit that withdrawn marriages may be closer to dissolution.…”
Section: Empirical Perspectivesmentioning
confidence: 99%
“…Cummings, Pellegrini, Notarius, & Cummings, 1989; O'Brien, Margolin, John, & Krueger, 1991). In a similar vein, Katz and Gottman (1994) use the developmental context of the marriage to account for their finding that a withdrawn marital interaction style, but not a "hot" engaged style, is associated with child anger; they posit that withdrawn marriages may be closer to dissolution.…”
Section: Empirical Perspectivesmentioning
confidence: 99%
“…Background anger (BA) is defined as the presence of a verbal, nonverbal, or physical conflict between two or more individuals (typically adults) that children observe as bystanders 20,21 . Omli and LaVoi astutely consider the importance of examining the nature, frequency, and outcomes associated with background anger with the understanding that although conflicts in youth sport are often reported between adults (parents, coaches, officials), they occur in the presence of children 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cummings [20] reported that in dysfunctional family settings, young children responded to BA with heightened symptoms of stress, negative emotional responses, and by becoming more aggressive with peers. Additionally, Cummings et al [21] report that all angry exchanges, even those that are non-verbal, evoke negative emotions in children. While physical-verbal altercations are interpreted as the most consequential in regards to children's emotions, unresolved anger induces more distress in children than resolved anger.…”
Section: Introductionmentioning
confidence: 99%
“…(Duncan & BrooksGunn, 2000). A nivel de las relaciones del cuidador principal, elementos como el soporte social y la calidad de la relación de pareja (Conger et al, 2002;Cummings, Pellegrini, Notarius, & Cummings, 1989;McLoyd, 1998). A nivel del cuidador principal, incluir la calidad del apego del adulto y el nivel de sensibilidad materna.…”
Section: Discussionunclassified